1999
DOI: 10.1111/1467-8624.00105
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent‐Parent Conflict in Middle‐Class African American Families

Abstract: Everyday conflicts between adolescents and parents were examined in 95 middle-class African American families, 44 with preadolescents and 51 with early adolescents, who were further divided into two groups based on family income. The incidence, frequency, and intensity of conflicts were assessed using the Issues Checklist, and content, justifications, and resolutions were coded from individual interviews. Conflicts were relatively frequent, low in intensity, and occurred over issues such as the adolescent's ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
150
0
3

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(170 citation statements)
references
References 40 publications
17
150
0
3
Order By: Relevance
“…For example, parental appeals to prudential justifications -including concerns about health and safety -to resolve conflicts with their teens, have been found to be characteristic of certain subgroups of parents, particularly African American parents of male adolescents (Smetana et al, 2003 ). Along those lines, it has been suggested that parental inhibition of autonomy -whether it is defined in behavioral terms (e.g., strict rules and consequences), and/or in cognitive terms (e.g., discouragement of individual expression) -is potentially more appropriate when greater independence may pose increased threats to the adolescent ' s well -being (Dubrow & Garbarino, 1989 ;Furstenberg, 1993 ;Smetana & Gaines, 1999 ). In less risky contexts, however, these same autonomy -inhibiting behaviors might be more likely to reflect a maladaptive parental reluctance to allow normative autonomy development to proceed (Baldwin, Baldwin, & Cole, 1990 ).…”
Section: Attachment Autonomy and Socioeconomic Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, parental appeals to prudential justifications -including concerns about health and safety -to resolve conflicts with their teens, have been found to be characteristic of certain subgroups of parents, particularly African American parents of male adolescents (Smetana et al, 2003 ). Along those lines, it has been suggested that parental inhibition of autonomy -whether it is defined in behavioral terms (e.g., strict rules and consequences), and/or in cognitive terms (e.g., discouragement of individual expression) -is potentially more appropriate when greater independence may pose increased threats to the adolescent ' s well -being (Dubrow & Garbarino, 1989 ;Furstenberg, 1993 ;Smetana & Gaines, 1999 ). In less risky contexts, however, these same autonomy -inhibiting behaviors might be more likely to reflect a maladaptive parental reluctance to allow normative autonomy development to proceed (Baldwin, Baldwin, & Cole, 1990 ).…”
Section: Attachment Autonomy and Socioeconomic Contextmentioning
confidence: 99%
“…Research focusing on parenting across social contexts does indicate that parents in high -risk contexts (e.g., lower SES) are more likely to use strategies emphasizing conformity and obedience, rather than those that promote independence and autonomy (Bartz & Levine, 1978 ;Dornbusch, Ritter, Leiderman, Roberts, & Fraleigh, 1987 ;Dubrow & Garbarino, 1989 ;Harkness & Super, 1995 ;Kelley, SanchezHucles, & Walker, 1993 ). Even among a sample of middle -income African American families, for example, parental power assertion (and adolescents ' acceptance of it) is more common among the lower income ranges, whereas joint parent -adolescent decision making and adolescent rejection of parental authority are more common among the higher income families (Smetana, 2000 ;Smetana & Gaines, 1999 ). Parental approaches to autonomy granting have also been found to vary along ethnic and cultural lines, and the picture is further complicated when families from cultures that tend to place less emphasis on autonomy immigrate to places where autonomy is highly valued (Feldman & Quatman, 1988 ;Feldman & Wood, 1994 ;Fuligni, 1998 ;Rosenthal & Feldman, 1990 ).…”
Section: Attachment Autonomy and Socioeconomic Contextmentioning
confidence: 99%
“…Research investigating conflictual interactions between parents and their children during this developmental time period is sparse at best. In addition, despite a growing literature on families of different ethnic and economic backgrounds (e.g., Cauce, Hiraga, Graves, & Gonzales, 1996;Conger, Ge, Elder, Lorenz, & Simons, 1994;Fuligni, 1998;McLoyd & Smith, 2002;Smetana & Gaines, 1999) Children who enter adolescence with more conflictual relationships have been found to be at greater risk for more severe parent-child problems and poorer child outcomes during adolescence (Steinberg, 2001). In prior studies, both positive and negative emotional expressions and conflicts were more common in mother-child than in father-child interactions (Russell & Russell, 1987), a pattern that persists into adolescence (Collins & Laursen, 1992).…”
mentioning
confidence: 99%
“…subject of disputes between parents and their adolescents (Smetana, 1989;Smetana and Asquith, 1994;Smetana and Gaines, 1999). Similarly, adolescents and parents tend to view parental control as legitimate when it is exerted over children's actions that have prudential consequences for the health and safety of the child or pertain to the general conventions of society (Smetana, 1989(Smetana, , 1995Smetana and Asquith, 1994;Smetana and Gaines, 1999;Tisak and Tisak, 1990).…”
mentioning
confidence: 99%